STRATEGI PENGELOLAAN KAWASAN HUTAN PRODUKSI AB (Afgeschreven djati-Bosch) DI KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - , MULDALYANTO; , Dr. Ir. Ris Hadi Purwanto, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Uncertainty about designation of AB production forest area emerged from the stipulation of Ministerial Decree of Minister of Forestry No. 197/Kpts-II/2000. As the consequences of uncertainty of forest area, there is no confirmation of its management area. The aims of the research are: (1) to find out the certainty and condition of AB forest area